Հեքիաթի ժանրակազմութեան հետագիծը Օշականի մօտ եւ Օշականից դուրս - Դանիէլեան, Սուրէն (տպ. Atlas)
The paper examines Hagop Oshagan’s preferential details of the fairy tale. It focuses on Oshagan’s short and long literary prose in the compiled volume Khorhurtneru mehyone (Temple of Mysteries) published in 1922, as well as the two novels written at the end of his life, Gyankin bes (Like Life) and Osgi Orone, (which Oshagan considered fairy tales). Naturally, Oshagan’s fairy tales are linked on the one hand to the classical tradition of Armenian fairy tales developed by Ghazaros Aghayan, Rupen Zartarian, Telgadintsi, Mesho Kegham, and Hovhannes Toumanian, while on the other hand they bring forth unique features, which enable us to talk about Oshagan’s path of developing fairy tales. The paper takes into account the pictorial as well as the theoretical perceptions of both Armenian and international fairytale writers (Taniel Varoujan, Rupen Sevag, Vahan Tekeyan, Honore de Balzac, Marcel Proust and others). The paper is developed through important bibliographical information, textual analyses and theoretical generalisations. It highlights the definition Oshagan gave to the genre, concerning the critical layers of the correlation of fairy tale and life, and compares these to the approaches of Shahan Shahnur, Vahe Oshagan, Sdepan Topchian and others. The author notes that the fairy tales of Oshagan represent a period in his creative life and open up a unique window to see his world perception and stable preferences, which go beyond the limitations of the genre, penetrate into the world of the novel and play an important role in depicting the full picture of his literary creation.
Keywords: Գրականութիւն; Բանահիւսութիւն